O tropeirismo de porcos : processos mercantis e dinâmicas sócio-culturais na região nordeste do Rio Grande do Sul nas primeiras décadas do século XX - Silva, Sueli Maria da (2006)
The present study, of regional historical character, analyzes and it describes the tropeirismo of pigs that happened in the Northeast area of the state of Big Rio of the South, especially to the north of the municipal district of Lagoa Vermelha, in the period from 1920 to 1940 and to still analyze its correlations with the appearance of the agroindústrias of the Oeste catarinense to Perdigão, the Sadia and also the Majestade in the municipal district of Sananduva /RS. That singular tropeirismo became a seasonal practice in the area of the forests, where the forests of araucarias prevailed and that received significant flow of Italian migrants and its descendants came from of the Old Colonies of the State. Subject of different cultures they mixed in that space and in the activities you work, they looked for to break with the isolation and to reach the markets to exchange its production. For that local references were used, newspapers, published works, and especially the oral sources, that made possible the materialization of the research. With that study it was possible to reconstitute peculiar aspects of the tropeirismo of pigs, ressignificar the work carried out by the tropeiros, contextualizar the processes socioeconômicos and cultural of the area in the first half of the century XX, to understand the presence of complex close agroindustriais to the area and to also join new registrations to the regional history